Agent-based knowledge extraction services inside enterprise data warehousing systems environments - Lourenço, Anália Maria Garcia (2001)
During their lifetimes, enterprises have been storing and maintaining huge amounts of business and operational information. As time passed their information repositories grown almost exponentially and they have typically got "drown" in data. So, they felt the urge for more suitable systems, capable of gathering, treating and storing this data avalanche in appropriated manners. Therefore, it is necessary to conceive and implant adequate analytical systems, capable of dealing with this huge potential of information in the best way, and providing new knowledge about the activities of organizations. Taking these real scenarios into account, we designed and developed a multi-agent system specially conceived to support knowledge extraction processes over data warehousing systems, covering the definition and preparation of the data repositories to be mined, till the visualization and manipulation of the results.